Review of previously published ambient air respirable crystalline silica concentration data for use in risk assessment of mineral industry sources - Richards, John R.; Brozell, Todd T. (Frontiers in Public Health, 2025)
This paper is part of a set of papers concerning the possible health implications of ambient respirable crystalline silica beyond the fencelines of mineral industry sources such as frac sand, construction sand, crushed stone, and specialty silica product plants. Previously published ambient respirable crystalline silica data relevant to mineral industry sources are reviewed to identify the typical and maximum downwind ambient respirable crystalline silica concentrations expected beyond facility fencelines. These typical and maximum downwind concentrations can be used in risk assessment studies. Relevant RCS facility downwind and upwind ambient data sets previously compiled by the authors, state regulatory agencies, the Agency for Toxic Substances and Disease Registration (ASTDR), and academic researchers are reviewed. Emphasis is placed on data sets compiled in multi-year sampling programs that take into account seasonal variations and facility operational variations. To the extent possible, data from different geographic areas are included to account for differing background (upwind) concentrations. The ambient RCS data are condensed to yield mean and maximum long-term average concentrations that can be used in risk assessment studies. There is a high degree of consistency in the RCS concentration data published by numerous researchers at a wide variety of mineral industry facilities. The authors recommend a mean concentration of 0.28 μg/m3 as an estimate of the long term average RCS concentration downwind of the fencelines of typical mineral industry facilities and a maximum concentration of 1.5 μg/m3 as an estimate of 95% upper confidence level of the mean RCS concentration downwind of the fencelines of especially large mineral industry facilities and/or those facilities where the very hilly terrain limit dispersion of facility emissions. The authors recommend a mean concentration of 0.22 μg/m3 as an estimate of the typical long term average background concentrations. If there are community health concerns at the RCS concentrations in the range of 0.22 to 0.28 μg/m3, new measurement procedures that provide higher 24-h sample volumes and/or more sensitive analytical techniques would be needed to provide accurate community exposure data.